PENGEMBANGAN MEDIA PEMBELAJARAN FISIKA DENGAN MENGGUNAKAN APLIKASI ARTICULATE STORYLINE 3 PADA MATERI HUKUM NEWTON UNTUK KELAS X - Nadia Aprilia; Azizahwati Azizahwati; Azhar Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to design and produce physics learning media usingthe Articulate Storyline 3 application on Newton's law material for valid class X. Theresearch method used is research and development or Research and Development withthe ADDIE development model. The ADDIE stage was carried out in Analysis, Design,and Development. Media validation is seen from 5 aspects, namely the subject matteraspect to see the suitability of the material with the initial purpose of making theprogram, the auxiliary information aspect to see any additional information that is notdirectly related to the material, the interface aspect to see the product display, thenavigation aspect to see the consistency of the navigation used and the pedagogy aspectto see the suitability of the competencies used. The results showed that the physicslearning media using the Articulate Storyline 3 application on Newton's law materialfor classes was valid.Key Words: Articulate Storyline 3, Learning Media, Newton’s Law